Bi‐Deficiency Leading to High‐Performance in Mg3(Sb,Bi)2‐Based Thermoelectric Materials - Li, Jing‐Wei; Liu, Weishu; Xu, Wei; Zhuang, Hua‐Lu; Han, Zhijia; Jiang, Feng; Zhang, Peng; Hu, Haihua; Gao, Hanbin; Jiang, Yilin; Cai, Bowen; Pei, Jun; et al. (Advanced Materials, 2023)
Mg3(Sb,Bi)2 is a potential nearly‐room temperature thermoelectric compound composed of earth‐abundant elements. However, complex defect tuning and exceptional microstructural control are required. Prior studies have confirmed the detrimental effect of Mg vacancies (VMg) in Mg3(Sb,Bi)2. This study proposes an approach to mitigating the negative scattering effect of VMg by Bi deficiency, synergistically modulating the electrical and thermal transport properties to enhance the thermoelectric performance. Positron annihilation spectrometry and Cs‐corrected scanning transmission electron microscopy analyses indicated that the VMg tends to coalesce due to the introduced Bi vacancies (VBi). The defects created by Bi deficiency effectively weaken the scattering of electrons from the intrinsic VMg and enhance phonon scattering. A peak zT of 1.82 at 773 K and high conversion efficiency of 11.3% at ∆T = 473 K are achieved in the optimized composition of Mg3(Sb,Bi)2 by tuning the defect combination. This work demonstrates a feasible and effective approach to improving the performance of Mg3(Sb,Bi)2 as an emerging thermoelectric material. The formation and tuning of complex defects can effectively enhance the thermoelectric performance of Mg3(Sb,Bi)2. This work proposes an approach to mitigate the negative scattering effect of Mg vacancies by Bi deficiency. The heterovalent vacancies provide a strong phonon scattering, leading to a significant reduction of the lattice thermal conductivity and a superior zT.